Behavior of mulberry (Morus alba L.) and its impact on the animal production and the breeding of silkworms in Cuba - Mart?n, Giraldo; Pent?n, Gertrudis; Noda, Yolai; Contino, Yuv?n; D?az, Maykelis; Ojeda, F.; Jim?nez, F. A.; L?pez, O.; Agramonte, D.; Milera, Milagros; Prieto, Marlene (Cuban Journal of Agricultural Science, 2014)
Mulberry has excellent nutritional qualities, like its high content of proteins and energy, so it has been offered as food to many species of animals since the 90?s. The ?Estaci?n Experimental Indio Hatuey? has a gene bank of 20 varieties from Costa Rica, Brazil, South Korea, China and Spain. Studies have been directed to evaluate the behavior of this arboreous plant under different edaphoclimatic conditions, to meet the effect of the factors of the agronomic management in order to determine the potential of the total and edible biomass production, to characterize the bromatological and phytochemical composition of the varieties, determine the intake, digestibility, the animal response and its medical use, as well as to develop the breeding of silkworms. Results state that this plant has a great ability of adapting to different edaphoclimatic conditions. It can produce between 10 and 12 t of DM/ha/year (edible biomass), from 20 to 25 % of CP and the DM digestibility surpasses the 80%. Indicators of liveweight gain and milk production show similar levels to those obtained with the use of imported concentrates. The anti-inflammatory, cicatrizing, antimicrobial and anthelmintic properties of this plant have been demonstrated. Besides, with a proper management of the specie, it is possible to develop the breeding of silkworms for commercial purposes, without the influence of the climate as a limitation for the development of this insect. This known specie is used all over the country by companies, cooperatives and producers, and it has a great acceptance, mainly for feeding smaller species from different cattle subprograms of the urban agriculture. Key words: gene bank, feeding, medicinal, sericulture.